Communicative Translation Strategy in the Children's Story Bint Al-Ṣabbāgh by Kamil Kailani - Rusyda, Rizka Kamilatu (Fakultas Adab dan Humaniora, Universitas Islam Negeri Syarif Hidayatullah Jakarta, 2024)
The limited number of Arabic-to-Indonesian children's storybooks that apply communicative translation strategies poses a challenge in developing children’s literacy rich in moral values. This article aims to analyze communicative translation strategies in the children's story Bint al-Ṣabbāgh by Kamil Kailani, emphasizing acceptability and readability for young readers. This study employed a descriptive qualitative method by classifying and analyzing data based on communicative translation strategies. Ten core data segments were selected from the source text as they represent the narrative’s main structure. Each data segment was analyzed using two to three communicative translation strategies simultaneously, including ḥaẓf (omission of non-essential elements such as prepositions “di-” and “ke-”), taqdīm wa ta’khīr (shifting the order of subjects and predicates), tabdīl (substituting words for more communicative expressions), and ziyādah (adding explanatory elements relevant to the target culture). The findings indicate that communicative strategies can produce flexible, natural translations that are easily understood by children without diminishing the moral messages of the source text. Each strategy functions to adjust structure and meaning to align with the linguistic habits of Indonesian children. This study contributes to the practice of translating children's literature, especially from Arabic texts, and supports the development of educationally rich children’s books that are culturally adaptive to the target audience.